Techno-Economical Evaluation of Extractive Distillation Process for Isopropanol Dehydration with Different Extractive Solvents - Mihaela Neagu; Diana-Luciana Cursaru (Applied Sciences)
In recent decades, the attention of researchers has been directed towards the study of the dehydration of isopropanol (IPA) through different techniques. Besides its multiple uses in the chemical industry, IPA is also a potential bio-component in eco-friendly gasolines. Extractive distillation is a successful technique for separating IPA from a minimum boiling azeotrope with water. However, the major challenge is the production of fuel-grade IPA (minimum 99.92 mol%) with low expenses. As a consequent step in the investigation of IPA dehydration with propylene glycol as extractive solvent, the present study compares its efficiency and economic viability with two other extractive solvents, namely ethylene glycol (EG) and dimethyl sulfoxide (DMSO). A systematic and comprehensive methodology was developed to design a three-column extractive distillation (TCED) for each investigated solvent. A techno-economic assessment of all the investigated processes concluded that ethylene glycol, followed by propylene glycol, seems to be the most promising solvent in the IPA dehydration process. Further, the heat integration of hot streams (SH flowsheets) demonstrated improvements over 17% in the case of ethylene glycol solvent, around 16% in the case of propylene glycol (PG) solvent, and only 10% (in the case of DMSO solvent) reduction in utility consumption, improving the energy efficiency of TCED processes. Furthermore, SH flowsheets yield a 14% cost saving obtained in terms of total annualized cost (TAC) and, respectively, 8.69%, by comparison with TCED processes. In the case of DMSO solvent, the TAC reduction is only 3.54% due to the capital cost, which has an increase of 3% mainly due to the high solvent cost.